Parallel processing and applied mathematics. 11th International Conference, PPAM 2015, Krakow, Poland, September 6-9, 2015, Revised selected papers /: 11th International Conference, PPAM 2015, Krakow, Poland, September 6-9, 2015, Revised selected papers. Part I : (2016) - Unknown
No abstract available